(3HMhK GdJShjb (B:s (3eONd fXQj hJWHjbj (B/s - (3GdWGFj, MejO YHO GdfHjs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2008)
- (3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B: (3fXGe GdeYdheGJ GdJShjbjI fXGe GdeYdheGJ GdJShjbjI ,ebOeI aj GdHMK GdJShjbj,,NWhGJ EYOGO GdHMK GdJShjbj(B.(3GdGWGQ GdejOGfj dHMhK GdJShjb s
(3HjHdjhZQGajG fgGjI cd aUd ; edGMb fgGjI cd aUd s
Keywords: (3GdJShjbs